Growth Performance, Feed Efficiency and Ingestive Behavior of Sahiwal Calves Divergently Selected for Residual Feed Intake - Singh, Anil Kumar; Kumar, Muneendra; Kumar, Vinod; Roy, Debashis; Kushwaha, Raju; Vaswani, Shalini; Kumar, Avinash (Indian Journal of Animal Nutrition, 2019)
This study aimed to evaluate differences in performance, feed utilization efficiency, and ingestive behavior between low and high residual feed intake (RFI) growing cattle. Eighteen growing female Sahiwal calves (age 10Â±4 months, body weight 100Â±45 kg) were fed individually using ad libitum feeding of total mixed ration for a period of 90 days. RFI varied from -0.53 to 0.40 kg dry matter (DM)/day with a mean RFI of -0.27 to 0.17 kg DM/day in low and high RFI calves, respectively. Significant (P<0.001) differences between low and high RFI calves were observed for daily DM intake (DMI). Calves with low RFI consumed 26% less DM compared to high RFI group yet gaining at similar rate. Low RFI calves needed 35% less metabolizable energy for body maintenance (MEm) compared to high RFI calves while metabolizable energy for gain (MEg) was similar among both groups. Low RFI calves digest feed more efficiently than high RFI calves. Low RFI calves were also more efficient in feed conversion, feed efficiency, Kleiber ratio (KR), and relative growth rate (RGR) than high RFI calves. Low RFI calves consumed less feed than high RFI calves therefore, spent less time in feeding, rumination, and chewing. RFI was positively correlated with DMI, MEm and MEg, and gain while negatively correlated with traditional feed efficiency measures and ingestive behavior. This study suggests that low RFI calves are more efficient because they eat less and require less energy for physical activity and feeding pattern.